Experimental investigation on the effect of varying fiber mix proportion on the mechanical and thermal performances of fiber-reinforced self-compacting concrete under hydrocarbon fire condition - Jani, N.M. (MDPI AG, 2020)
This paper presents the experimental analysis of the effects of simulated hydrocarbon fire exposure on the mechanical properties and the heat transmission in fiber-reinforced self-compacting concrete, FR-SCC. For that purpose, 300-mm thick, and 1200-mm square-shaped slabs were cast. Basalt and polyvinyl alcohol (PVA) fibers were added using the content of 1, 1.5, and 2 in self-compacting concrete. For investigating the heat transmission within 300-mm thick slabs, five external thermocouples were installed at the unexposed face to the fire of the slabs. Similarly, eleven internal thermocouples were installed at an interval of 25 mm throughout the slab thickness. It has been found that fibers have shown better insulation than the controlled concrete; the unexposed to fire surface of FR-SCC showed temperatures lower by ten degree Celcius than the controlled concrete. Compressive strength results showed that fiber addition caused a higher reduction in strength because of softening and stiffness reduction due to high-temperature exposure. After 120 min of fire exposure, basalt fibers caused an average reduction of 30 in the compressive strength, and PVA fibers caused an average reduction of 25. Whereas, the addition of fibers improved the split cylindrical tensile strength even after exposure to 120 min of fire exposure in comparison with the unreinforced samples. Â© 2020 by the authors.